(untitled) (Research, Society and Development, 2023)
Nowadays there is a growing world demand for grains, and the corn crop stands out as an important source of human and animal nutrition. To improve productivity and reduce the use of synthetic agricultural inputs, bioinoculants were created, which allow low-cost production without environmental contamination, improving soil fertility and biodiversity. The objective of this study was to evaluate the efficiency of the ILP system, and the use of Bioinoculants and Organic Fertilization in the performance of the corn crop, as sustainable strategies for the best use of the land in semi-arid regions, as is the case of the Jequitinhonha Valley. The experiment was carried out at IFNMG - Araçuaí campus, using BRS 3046 corn and cv. BRS Tamani, NPK chemical fertilizer, composed of bovine manure and BiomaPhos® and Azotrop® bionocculants. In this study, the effect of different fertilization schemes on the growth and productivity of BRS 3046 hybrid corn plants was evaluated, analyzing the following characteristics: Plant height, stem diameter, plant population, incidence of pests and diseases, estimate of productivity and physiological maturity at 50 and 60 days after sowing. The results are suggestive that the supply of nutrients through the addition of bioinoculants and fertilization of corn plants, enhances the performance of the crop. However, the last harvest had an atypical precipitation in the region studied, making it essential to repeat this experiment in the coming years.